1966
DOI: 10.1111/j.2153-3490.1966.tb00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of radon and thoron decay product concentrations in the surface layer of the atmosphere and their washout by precipitations

Abstract: Data on diurnal variations of radon and thoron decay product concentrations in the surface layer of the atmosphere in the Moscow region are given. It is noted that the maximum of radon exhalation from the soil occurred at night. (Measurements were carried out in summer in dry weather.) The strongest upset of radioactive equilibrium between radon daughter products was observed in the first half of night and in the day-time.From the degree of non-equilibrium between RaA:RaB:RaC during the rain the constant of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

1972
1972
2012
2012

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 2 publications
2
13
0
1
Order By: Relevance
“…These conditions in the wintertime are sustained by the shallow boundary layer height (500Á900 m) along the Gangetic Plain (Nair et al, 2007). The 222 Rn activity in the ambient air has been used for estimating the planetary boundary layer dynamics and particularly the mixing height of regional pollutants (Malakhov et al, 1966;Levin et al, 2002;Zahorowski et al, 2005). This approach is usually adopted in view of the fact that the escape rate of 222 Rn is nearly constant over the land areas (Â1 atom cm (2 s (1 ) (Wilkening and Clements, 1975;Turekian and Graustein, 2003;Baskaran, 2011).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These conditions in the wintertime are sustained by the shallow boundary layer height (500Á900 m) along the Gangetic Plain (Nair et al, 2007). The 222 Rn activity in the ambient air has been used for estimating the planetary boundary layer dynamics and particularly the mixing height of regional pollutants (Malakhov et al, 1966;Levin et al, 2002;Zahorowski et al, 2005). This approach is usually adopted in view of the fact that the escape rate of 222 Rn is nearly constant over the land areas (Â1 atom cm (2 s (1 ) (Wilkening and Clements, 1975;Turekian and Graustein, 2003;Baskaran, 2011).…”
Section: Resultsmentioning
confidence: 98%
“…Studies on soil samples from different lithological units have suggested that the distribution of radionuclides depends on rock formation, their chemical properties and sample origin (Malakhov et al, 1966;Rao et al, 1996;Levin et al, 2002;Ramola et al, 2008;Baskaran, 2011). Rani and Singh (2005) (Singh et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Possible disequilibrium of radon-222 and the short-lived daughters is not so obvious but the frequent occurrence is well established [28,43,44,31,23,50]. The extent of disequilibrium is in first order due to the radioactive decay in concurrence with vertical diffusion.…”
Section: ]mentioning
confidence: 99%
“…The extent of disequilibrium is in first order due to the radioactive decay in concurrence with vertical diffusion. Good approach to equilibrium is reached especially with near-surface inversions as often observed in the morning [43,65,50]. The model is one-dimensional with certain assumptions on the eddy diffusion coefficient and its dependence on altitude.…”
Section: ]mentioning
confidence: 99%
See 1 more Smart Citation